J‐SUPPORT research policy for oral mucositis associated with cancer treatment. (12th June 2022) - Yokota, Tomoya; Ueno, Takao; Soga, Yoshihiko; Ishiki, Hiroto; Uezono, Yasuhito; Mori, Takehiko; Zenda, Sadamoto; Uchitomi, Yosuke
Abstract: Background: Oral mucositis is one of the main areas of research in supportive and palliative care of cancer patients. However, the methodology of prospective clinical trials on oral mucositis has not been established, despite its uniqueness. Here, we propose a novel research policy on oral mucositis, including an implementable set of recommendations for researchers conducting clinical trials. Methods: The first draft was developed by an expert panel of six specialists from the Japanese Supportive, Palliative, and Psychosocial Care Study Group. A provisional draft was developed after review by the following medical societies: the Japanese Association of Supportive Care in Cancer, the Japanese Association of Oral Supportive Care in Cancer, the Japanese Cancer Association, and the receipt of public comments. Results: The research policy on oral mucositis mainly consists of the following components: (i) definition of oral mucositis; (ii) characteristics of oral mucositis; (iii) characteristics of oral mucositis research; (iv) target population for oral mucositis research; (v) endpoints and assessment measures in oral mucositis; (vi) eligibility criteria; (vii) research design; (viii) minimally recommended intervention in oral mucositis research as a supplement. The final policy (Ver1.0) was completed on August 16, 2021. Conclusions: This policy may serve as a significant reference for planning and conducting clinical trials for the management of oral mucositis. Abstract : An expert panel of the Japanese Supportive, Palliative, and Psychosocial Care Study Group (J‐SUPPORT) developed a specific and precise policy for clinical studies on oral mucositis induced by cancer therapy. The contents of this policy were systematically organized according to the items in the study protocol, including endpoints, eligibility criteria, assessment measures, and research design. This policy is useful for the researchers in the field of oral mucositis research to conduct high‐quality clinical studies and report reliable evidence.